Parallel Lepp-Bisection Algorithm over Distributed Memory Systems - Rodriguez, Pedrio A.; Rivara, Maria Cecilia (Proceedings - International Conference of the Chilean Computer Science Society, 2013)
We discuss a parallel Lepp-bisection algorithm for two-dimensional mesh refinement over distributed memory systems. We discuss the subdivision of the mesh and the management of interface refinement and communication. We also study the empirical algorithm behavior.